PEMBINAAN TERHADAP TERPIDANA LANJUT USIA DI LEMBAGA PEMASYARAKATAN KLAS IIA JAMBI - M. Chairul Idrah (Universitas Batanghari Jambi, 2013)
Coaching program for elderly inmates in Prison Class IIA Jambi conducted under the provisions of Penal Law, but the implementation is tailored to the age, ability and needs of the elderly concerned. However, because of the circumstances they are in general already senile, frail, deaf and suffering from acute disease, then the coaching program that has been programmed by the prison to them, can not be effectively implemented so that the purpose of punishment can not be done. It is necessary for the conception of sentencing policy should be applied to elderly criminals are adopting the provisions of the Penal Code governing the criminal reduction and alternative sentencing and punishment provisions of the Criminal Code Bill to the elderly so as to obtain a conviction against setting elderly criminals are able to meet the statutory objectives and sentencing goals effectively.Keyword : Coaching, offenders, Correctional Institutions